2020
DOI: 10.1159/000507608
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Silicone Oil into the Orbit and Eyelid as a Cyst

Abstract: A 7-year-old female presented with left upper eyelid swelling following pars plana deep vitrectomy and silicone oil injection 1 year before admission. The left upper eyelid had mechanical ptosis and on palpation there was a lobulated mobile mass in the lateral portion of eyelid. Computed topography scan showed multiple isodense masses with silicone oil in vitreous in the eyelid and orbit; histopathology after excisional biopsy proved the silicone oil migration. Silicone oil migration followed by vitrectomy may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In addition, it has been reported that intraocular silicone oil has an association with several complications, such as the development of cataracts, glaucoma, and epiretinal and subretinal fibrosis [ 10 ] and migration of silicone oil to extraocular muscle, as described in this report. Its emulsification and dispersion properties can explain silicone oil migration to numerous ocular structures [ 11 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, it has been reported that intraocular silicone oil has an association with several complications, such as the development of cataracts, glaucoma, and epiretinal and subretinal fibrosis [ 10 ] and migration of silicone oil to extraocular muscle, as described in this report. Its emulsification and dispersion properties can explain silicone oil migration to numerous ocular structures [ 11 ].…”
Section: Discussionmentioning
confidence: 57%
“…However, various reasons for this can be postulated. One of the leading theories is that intraocular silicone oil may leak through pars plana vitrectomy ports during or following posterior segment surgery [ 10 ]. This is thought to be aggravated by postoperative spikes in intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone oil is commonly used for the surgical treatment of giant retinal tears and retinal detachment[ 1 ]. However, its use is associated with complications such as cataract formation, silicone oil keratopathy, emulsification with glaucoma, intraconjunctival oil inclusion cysts, subretinal oil accumulation, membrane reproliferation beneath the oil interface, and optic atrophy[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some radiologists must be aware of the typical locations of SiO migration on computed tomography (CT) [8] . The SiO diffuses posteriorly and migrates into the retina and the pathways for vision (optic nerve, chiasm, and tract), and even its progression into the subarachnoidal and ventricular system [9][10][11] . One published study attempted to report the incidence of retrolaminar migration of SiO and present radiologic findings and clinical features based on unenhanced CT scans of the head [12] .…”
Section: Introductionmentioning
confidence: 99%